FBOS: FREQUENCY BASED OPTIMIZATION STRATEGY FOR THREAD POOL SYSTEM - Bahadur, F.; Naeem, M.; Javed, M.; Wahab, A. (The Nucleus, 2014)
Competitive multithreading models for constructing server side applications are thread-per-request and thread pool. Thread pool architecture is more efficient because of its pre-spawning and recycling a pool of threads. But tuning the thread pool system at the optimal level and dynamically changing its size is still a challenging task. This paper presents a Thread Pool System which is equipped with a dynamic optimization strategy named Frequency Based Optimization Strategy (FBOS) that reacts on the basis of client’s request frequencies. In this paper we also presented a comparison between the two best pool techniques and FBOS strategy with the help of a Request Simulator and the results of simulation have proved that FBOS is more responsive and efficient than other strategies.